Tax Reforms and Income Inequality in Former Yugoslav Countries: Escaping the Avant-Garde Neoliberalism in the Income Tax Policy - Žarković Rakić, Jelena; Vladisavljević, Marko (Panoeconomicus, 2021)
After the breakup of former Yugoslavia Croatia, Serbia and Slovenia followed different income tax reform trajectories that could explain currently different levels of income inequality in these countries. Our paper analyzes redistributive effects of introducing progressive tax systems, like the ones currently implemented in Slovenia and Croatia, in the Serbian context. Using microsimulation modeling and Survey on Income and Living Conditions data for 2017 our results suggest that implementation of both Croatian and Slovenian tax system would yield lower levels of income inequality and poverty if applied in Serbia. Slovenian system achieves larger decrease in inequality due to higher tax burden on the top incomes and brings significant increase in tax revenues. Croatian tax schedule achieves stronger decrease in poverty as more generous personal allowance exempt higher portions of low incomes from labour taxes. Key words: Progressive taxation, Inequality, Policy swapping, Microsimulation. JEL: C81, D63, H24.